A heterogeneidade discursiva em revistas de divulgação científica - Barbosa, Maria do Socorro Maia Fernandes (2008)
This research aiming at show an interpretative description about the form and function of Scientific Publication (SP) discursive genre, in two magazines of national circulation. We analyzed subjects published from 2004 to 2006, in the magazines Revista do Professor and Revista Nova Escola. We see at SP subjects reported discourses, into its two main presentation forms of other voices: direct discourse and indirect discourse. We have established some aims, first, we analyzing different forms to mark the discursive heterogeneity, by the reason the writer conceptualize an image of his/her interlocutor. The second one, we intend to look at the differences between marked heterogeneity according to the writer production, journalists and researchers, and finally, we investigate more or less occurrence of cited discourse, in what is concerned with different perspectives at communities that produce this kind of text. As theoretical background to our discussions we followed socio-historical perspective, its language and subject discourse conceptualizations. We did it mainly based on Bakhtin s works (1929; 1995; 2003). We were also based on theoretical discussions about discursive heterogeneity by Authier-Revuz (1990; 1998; 2004) and Maingueneau (1993; 2001). At analyzing the social dimensions of our data, we identified as relevant elements in the construction of the subjects (stories) the image that the writer (reporter) did/construct about his/her interlocutor as well as the use of different strategies, for example: the text produced by the journalists frequently use of direct discourse forms, while texts produced by researchers are almost fulfilled by indirect discourse. Beside this, texts are different in their social voices that are in their discourse. In the case of text produced by journalist are predominant the discursive scene of the school agents: teachers, students, parents, among others. Otherwise, in the texts produced by researchers already-said utterances, that in their majority of times, come from scientific discourse